On the (nonlinear) relationship between exchange rate uncertainty and trade: An investigation of US trade figures in the Group of Seven - Helmut Herwartz (Humboldt University of Berlin, Interdisciplinary Research Project 373: Quantification and Simulation of Economic Processes, 2003)
In this paper bilateral models formalizing monthly growth of US imports and exports are employed to investigate the potential of nonlinear relationships linking exchange rate uncertainty and trade growth. Parametric linear and nonlinear as well as semiparametric time series models are evaluated in terms of fitting and ex ante forecasting. The overall impact of exchange rate variations on trade growth is found to be weak. In periods of large exchange rate variations, trade growth forecasts gain from conditioning on volatility. Empirical results support the view that the relationship of interest might be nonlinear and, moreover, lacks homogeneity across countries and imports vs. exports
urn:nbn:de:kobv:11-10049730
Keywords: C22; F41; C14; F31; 330; Exchange rate volatility; international trade; ARCH; Group of Seven; forecasting; Wechselkurs; Volatilität; Aussenwirtschaft; Zeitreihenanalyse; ARCH-Modell; Nichtparametrisches Verfahren; Schätzung; Vereinigte Staaten; G7-Staaten